Differences in neurohormonal activity partially explain the obesity paradox in patients with heart failure: The role of sympathetic activation. (15th February 2015) - Farré, Núria; Aranyó, Júlia; Enjuanes, Cristina; Verdú-Rotellar, José María; Ruiz, Sonia; Gonzalez-Robledo, Gina; Meroño, Oona; de Ramon, Marta; Moliner, Pedro; Bruguera, Jordi; Comin-Colet, Josep
Abstract: Background: Obese patients with chronic Heart Failure (HF) have better outcome than their lean counterparts, although little is known about the pathophysiology of this obesity paradox. Our aim was to evaluate the hypothesis that patients with chronic HF and obesity (defined as body mass index (BMI) ≥ 30 kg / m 2 ), may have an attenuated neurohormonal activation in comparison with non-obese patients. Methods and results: The present study is the post-hoc analysis of a cohort of 742 chronic HF patients from a single-center study evaluating sympathetic activation by measuring baseline levels of norepinephrine (NE). Obesity was present in 33% of patients. Higher BMI and obesity were significantly associated with lower NE levels in multivariable linear regression models adjusted for covariates (p < 0.001). Addition to NE in multivariate Cox proportional hazard models attenuated the prognostic impact of BMI in terms of outcomes. Finally, when we explored the prognosis impact of raised NE levels (> 70th percentile) carrying out a separate analysis in obese and non-obese patients we found that in both groups NE remained a significant independent predictor of poorer outcomes, despite the lower NE levels in patients with chronic HF and obesity: all-cause mortality hazard ratio = 2.37 (95% confidence interval, 1.14–4.94) and hazard ratio = 1.59 (95% confidence interval, 1.05–2.4) in obese and non-obese respectively; and cardiovascular mortality hazard ratio = 3.08 (95% confidence interval, 1.05–9.01) in obese patients and hazard ratio = 2.08 (95% confidence interval, 1.42–3.05) in non-obese patients. Conclusion: Patients with chronic HF and obesity have significantly lower sympathetic activation. This finding may partially explain the obesity paradox described in chronic HF patients.